Growing up in North America: The economic well-being of children in Canada, the United States, and Mexico - Katherine Scott (Luxembourg Income Study (LIS), 2008)
Globalization is changing the landscape of childhood. As part of such change, North America is also becoming more economically, socially, and culturally integrated. It is against this backdrop of economic, social, and cultural transformation that the Children in North America Project is examining the well-being of the 120 million children across the continent. This paper examines the economic security of children across North America, looking at a range of measures, including family income, access to basic goods such as housing and health care, and the scope of public resources available to improve the economic security of families with children. Our findings confirm that there are tremendous disparities in the economic well-being of children across North America, both between and within the three countries. Even as the national economies recovered from economic crises in the early and mid-1990s and levels of child poverty started to fall, families at the top of the income ladder continued to pull away from the rest and incomes at the bottom stagnated or fell as was the case in Mexico. While the majority of children growing up in the United States and Canada enjoy a level of economic security not available to millions of Mexican children, the pattern of income inequality was common in each country.
Keywords: 330; Kinder; Lebensqualität; Grundbedürfnisse; Soziale Lage; Kanada; USA; Mexiko